Response surface optimization of multilayer graphene growth on alumina-supported bimetallic cobalt–nickel substrate - Alsaffar, May Ali; Abdul Rashid, Suraya; Ayodele, Bamidele Victor; Hamidon, Mohd Nizar; Md. Yasin, Faizah; Ismail, Ismayadi; Hosseini, Soraya; Babadi, Farahnaz Eghbali (Springer, 2020)
This study investigates the optimization of multilayer graphene (MLG) growth on Co–Ni/Al2O3 substrate. The MLG synthesized by chemical vapor deposition technique (CVD) was characterized using various instrument techniques. The surface area and pore volume of the MLG were estimated as ~ 642 m2/g and ~ 2.7 cm3/g, respectively. The Raman spectrometric analysis showed evidence of MLG. The effects of parameters such as temperature, Co–Ni composition and ethanol flow rate were investigated using response surface methodology (RSM) and central composite design. The maximum MLG yield of 77% was attained at optimum conditions of 800 °C, Co–Ni composition of 0.3/0.7 and ethanol flow rate of 11 ml/min. The analysis of variance (ANOVA) results showed that the RSM quadratic model is significant with a p value < 0.0001. The coefficient of determination (R2) values of 0.9694 revealed the reliability of the RSM model. The potential of CVD as a technique to synthesize MLG growth of a highly ordered crystallinity structure has been demonstrated in this study. The resulting MLG films are promising materials for the use in improving graphene-based electronics, sensing and energy devices.